1988
DOI: 10.1103/physrevlett.61.1906
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh-Energy Pulsed Emission from Hercules X-1 with Anomalous Air-Shower Muon Production

Abstract: A search for bursts of air-shower events from Hercules X-l at energies above 50 TeV during the calendar period 2 April 1986 to 5 July 1987 yielded two significant bursts, both occurring on UT 24 July 1986. The events during these bursts were pulsed with a period of 1.235 68 s, significantly different from estimates of the contemporaneous x-ray period. The probability that this represents random statistical fluctuations of the background is estimated to be 2xl0~5. The muon content of the burst events is anomalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(19 citation statements)
references
References 13 publications
1
18
0
Order By: Relevance
“…On the other hand, air-shower arrays are commonly used in the PeV energy region. The improvement in angular resolution based on accurate timing of the shower front is most powerful for isolating the small number of subset of showers arriving from the source direction, particularly in the light of claims for anomalous non-y signals with abundant muons from Cygnus X-3 [1, 4] or Hercules X-1 [5].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, air-shower arrays are commonly used in the PeV energy region. The improvement in angular resolution based on accurate timing of the shower front is most powerful for isolating the small number of subset of showers arriving from the source direction, particularly in the light of claims for anomalous non-y signals with abundant muons from Cygnus X-3 [1, 4] or Hercules X-1 [5].…”
Section: Introductionmentioning
confidence: 99%
“…The CYGNUS 1 and CASA 2 arrays are examples of such instruments. Despite an apparently anomalous signal from the Hercules X-1 3 , it is now generally believed that these instruments did not observe any convincing evidence for astrophysical sources of gamma rays at these high energies.…”
Section: Introductionmentioning
confidence: 96%
“…paper that this increase of the cross-section might help to explain the mysteriously large number of muons observed [83] in photon-induced cosmic air showers. Later detailed Monte Carlo calculations [84] showed that, while resolved photon processes might boost the muon yield by a factor of 2-3, they are not sufficient to explain the data by themselves.…”
Section: ) Minijets and Total Cross-sectionsmentioning
confidence: 99%